PENDAMPINGAN LITERASI MANAJEMEN JURNAL ILMIAH BERBASIS SISTEM AKREDITASI NASIONAL (ARJUNA) - Nasrum; Masykur Rauf (Merwinspy Publisher, 2026)
This mentoring activity aims to strengthen the capacity of scientific journal managers at Institut Agama Islam DDI Polewali Mandar, STIBA Makassar, Sekolah Tinggi Agama Islam DDI Makassar and Universitas Islam Ahmad Dahlan (UIAD) Sinjai in understanding and implementing the National Journal Accreditation (ARJUNA) standards. The mentoring program is carried out in stages through identifying the initial conditions of the journal, evaluating editorial governance, analyzing the quality of article substance, and training and practice in journal management based on Open Journal Systems (OJS). The evaluation results show that most partner journals face relatively similar obstacles, including suboptimal documentation of editorial policies and publication ethics, weak implementation of peer review, limited diversity of editors and reviewers, low quality of article readability, and inconsistent publication schedules. Further mentoring is directed at strengthening ARJUNA's literacy through the implementation of journal quality improvement strategies that adhere to best practices for SINTA 2-accredited journals. These strategies include developing more transparent and standardized journal policies, optimizing editor and reviewer functions, implementing a systematic and documented editorial process, improving article quality through stricter manuscript selection, and refining journal metadata and presentation. These activities have positive implications not only for the technical and administrative aspects of journal management but also for shifting the governance paradigm toward a more strategic, sustainable, and quality-oriented system. Therefore, this mentoring is a crucial part of the institutional learning process in preparing partner journals to improve their accreditation rankings toward SINTA 2.